Constituintes químicos de Macroptilium martii (Fabaceae): isolamento guiado por espectrometria de massas, caracterização e citotoxicidade - Souza, Ranna Beatris de Lima (2020)
The use of plants by human beings has been part of the organization of communities since the beginning, as food, a source of alternative treatment and for the promotion of health. This practice is still common in several peoples, being more evident in developing countries, but nowadays it has gained importance, as modern society has been exploring natural resources and their immense diversity of substances. Among the families found in the Caatinga, the plants of the Fabaceae family are the predominant and among them is the species Macroptilium martii (Benth.), Known as jaguar ear that occurs throughout the Northeast region. Due to the rare studies with this genus and the absence of chemical and pharmacological studies of the species, this work aims to carry out a phytochemical approach and monitor the cytotoxic potential from the crude ethanolic extract to the isolated substances of M. martii. The aerial parts of the species were collected between the municipalities of Monteiro and Sumé in Paraíba, after drying and spraying, an extraction of plant material with ethanol was carried out and subsequent liquid-liquid partition of the crude ethanolic extract, resulting in the hexane, chloroform, acetate phases of ethyl and n-butanolic. The ethyl acetate phase was analyzed by HPLC-MS / MS, presenting 12 main peaks, which were identified as being glycosylated flavonoids and saponins. This same phase was subjected to column chromatography with Sephadex-LH20, and one of its fractions (04) was analyzed by HPLC on an analytical scale and fractionated on a preparative scale, leading to the isolation of four substances: canferol-3-O-galactose-6''-O-rhamnose, isorhamnetin-3-O-galactose-6''- O-rhamnose, a protoalkaloid called 2 - [(carboxy-acetyl) amino] benzoic acid and a new glycosylated flavonoid not yet described in the literature Isorhamnetin-3-O-galactose-6''-O-rhamnose-4-O-galactose-2-methyl-butyric acid. The substances were identified by 1H and 13C NMR spectroscopy, two-dimensional and HR-ESI-EM. Cytotoxicity was evaluated from the ethanolic extract to the isolated substances of M. martii through the MTT reduction assay, using human tumor cell lines HCT-116 (human colorectal carcinoma), HeLa (cervical carcinoma), SKMEL (melanoma), PC-3 (prostate carcinoma) and MDA-MB-231 (human mammary adenocarcinoma), in addition to L929 (murine fibroblast) maintained in RPMI-1640 culture medium. This screening showed a result in which BSE - M. martii, AcOET Phase, AcOET-04, MM-04 and MM-02 did not show activity (1 to 20% inhibition), for the HCT-116, SKMEL, PC- 3 and MDA-MB-231 and only MM-04 and MM-02 showed very little activity (cell growth inhibition ranging from 20 to 50%) for the HeLa strain. Thus, it was observed that this screening had little promising results and only for a cell line. The results of this work, collaborated with the chemical and pharmacological knowledge of the genus Macroptilium and of the species Macroptilium martii, as well as directs for more studies to be carried out later